Grain Sorghum Response to Nitrogen Fertilizer following Cover Crops. (1st November 2017) - Fontes, Giovani Preza; Tomlinson, Peter J.; Roozeboom, Kraig L.; Ruiz Diaz, Dorivar A.
Abstract : Grain sorghum growth and development was affected by cover crop and N management. Sorghum–sudangrass cover crop prior to grain sorghum required N to maintain yield. Late maturing soybean cover crop increased grain sorghum yield at suboptimal N rates. Late maturing soybean cover crop, N fertilizer replacement value of 44 kg N ha –1 . Cover crops (CCs) can affect N fertilizer management by influencing nutrient cycling and N fertilizer requirement. Cropping systems with different CCs were established in 2007 to examine the response of sorghum [ Sorghum bicolor (L.) Moench]. Four CC treatments {summer legume, late‐maturing soybean [LMS; Glycine max (L.) Merr]; summer non‐legume, sorghum–sudangrass (SS; Sorghum bicolor × Sorghum bicolor var. sudanese); winter legume, crimson clover (CL; Trifolium incarnatum L.), and winter non‐legume, daikon radish (DR; Raphanus sativus L.)} as well as double‐crop soybean (DSB) and chemical‐fallow (CF) treatments were imposed after wheat ( Triticum aestivum L.) harvest in a wheat–sorghum–soybean cropping system. Five N rates (0, 45, 90, 135, and 180 kg N ha –1 ) were applied to sorghum within 2 wk of planting. Aboveground sorghum biomass was collected after physiological maturity to determine total N uptake and grain yield. The cropping system managed with LMS increased grain yield (>9%), compared to other CCs and CF with zero N application. Cropping systems including CL, DR, and DSB had similar effects on grain yield relative to CF when N fertilizer was applied. Increasing N rates significantly increased grain yield and N uptake of grain sorghum following SS, indicating that soil N was limited in this cropping system. The addition of LMS as a summer legume CC has the potential to contribute N and replace CF, thus improving management of N resources.